Proceedings of the Proceedings of the First Annual Conference of Economics, Business, and Social Science, ACEBISS 2019, 26 - 30 2020
DOI: 10.4108/eai.26-3-2019.2290684
|View full text |Cite
|
Sign up to set email alerts
|

Financial Ratio Analysis to Predict Financial Distress on Islamic Bank

Abstract: The purpose of this study was to determine the influence of Capital Adequacy Ratio, Financing to Deposite Ratio and Non-Performing Financing on Financial Distress. The object of research is 11 Islamic Commercial Banks registered in the Financial Services Authority (OJK) and Bank Indonesia (BI), with data from 2013 to 2017. The research was conducted with quantitative methods, to test the influence of independent variables on the dependent variable. Analysis of the data used is descriptive statistical analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Meanwhile, [5] stated that CAR has a positive and significant impact on Financial Distress. Furthermore, for Credit Risk, [3] and [6] stated that Credit Risk has a positive and significant impact on Financial Distress. Meanwhile, [8] stated that Credit Risk has a negative and significant impact on Financial Distress.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, [5] stated that CAR has a positive and significant impact on Financial Distress. Furthermore, for Credit Risk, [3] and [6] stated that Credit Risk has a positive and significant impact on Financial Distress. Meanwhile, [8] stated that Credit Risk has a negative and significant impact on Financial Distress.…”
Section: Related Workmentioning
confidence: 99%
“…Where the higher the CAR level, it indicates the bank has more credit to offer which can increase the bank's profits, so that the bank's ability to bear risks is getting better, and can reduce the possibility of financial distress. Under these conditions, CAR is considered to have a relationship with signaling theory, because increasing CAR can give a positive signal to investors [6]. H1: CAR has a negative and significant effect on Financial Distress.…”
Section: Financial Distressmentioning
confidence: 99%
See 1 more Smart Citation
“…If a bank experiences a loss (negative profit) but the capital ratio is high enough, the bank is said to be healthy even though the condition is the loss. Hasibuan et al (2020), Purbayati (2020) and Pamungkas et al (2021) revealed that there is an effect of the NPF ratio on FD. It is explained that high NPF causes banks to lose sources of income from profit-sharing income and profit margin income, resulting in a decrease in profits and the potential for FD.…”
Section: Introductionmentioning
confidence: 96%
“…It is explained that the FDR value shows the low liquidity capacity and total bank financing, thus risking FD. Meanwhile, research by D. W. Sari (2017), Erni & Imron (2019) and Hasibuan et al (2020) shows that the FDR ratio does not affect FD. It is evidenced by the FDR ratio value of less than 94.75%, so the potential for FD is low.…”
Section: Introductionmentioning
confidence: 99%